Unique patterns of molecular profiling between human prostate cancer LNCaP and PC-3 cells - Dozmorov, Mikhail G.; Hurst, Robert E.; Culkin, Daniel J.; Kropp, Bradley P.; Frank, Mark Barton; Osban, Jeanette; Penning, Trevor M.; Lin, Hsueh-Kung (The Prostate, 2009)
BACKGROUND Human prostate cancer LNCaP and PC‐3 cell lines have been extensively used to study prostate cancer progression and to develop therapeutic agents. Although LNCaP and PC‐3 cells are generally assumed to represent early and late stages of prostate cancer, respectively, there is limited information regarding gene expression patterns between these two cell lines and its relationship to prostate cancer. METHODS Comprehensive gene expression analysis was performed. Total RNA was isolated from cultured cells and hybridized to Illumina human BeadChips representing 24,526 transcripts. Bioinformatics analysis was applied to identify cell line specific genes as well as biological mechanisms, pathways, and functions related to the genes. RESULTS A total of 2,198 genes were differentially expressed between LNCaP and PC‐3 cells. Using a robust statistical analysis and high significance criteria, 115 and 188 genes were identified to be unique to LNCaP and PC‐3 cells, respectively. LNCaP cells maintained various metabolic pathways including a gene cluster that encodes UDP‐glucuronosyltransferases. Several transcription factors including Talα/β, GATA‐1, and c‐Myc/Max may be responsible for regulating LNCaP cell specific genes. By contrast, PC‐3 cells were characterized by their unique expression of cytoskeleton‐related genes and other genes including VEGFC, IL8, and TGFβ2. CONCLUSIONS This study showed that LNCaP and PC‐3 cells represent two distinct prostate cancer cell lineages. LNCaP cells retain many prostate cell specific properties, whereas PC‐3 cells have acquired a more aggressive phenotype. Future studies for prostate cancer research need to consider similarities and differences between these two cells and their relationship to prostate cancer. Prostate 69:1077–1090, 2009. © 2009 Wiley‐Liss, Inc.